Hold back the dawn - Ashley, Amanda (Zebra paranormal romance., 2019)
London<U+2019>s diversions hold no charm for Roan Cabrera. Despite his reputation as a scoundrel, he<U+2019>s in high demand among the city<U+2019>s most eligible young women. And though their blood can quench his undying thirst, none of them can fill the emptiness in his centuries-old soul. He finds solace only in easing the pain of those near death<U+2014>by helping them relive their most cherished memories <U+2026> The last thing Kathryn Winterbourne remembers is being struck by a carriage. When she awakens in a luxurious bed, she feels like she must have died and gone to heaven. But the man who has saved her is no angel. With his penetrating eyes, the darkly handsome Roan looks more like the devil himself. And when Kathryn is confronted with the truth about her mysterious hero, she<U+2019>ll have to decide whether to shutter her heart against him<U+2014>or give in to the thrill of his love <U+2026>